Macroeconomic Developments in Low-Income Developing Countries : 2014 Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
This report examines macroeconomic developments and related vulnerabilities in low-income developing countries (LIDCs)-a group of 60 countries that have markedly different economic features to higher income countries and are eligible for concessional financing from both the IMF and the World Bank. Collectively, they account for about one-fifth of the world's Population.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet